Representations of Iraqi identity in Iraqi plastic art after 2003 (Journal of the College of Basic Education, 2022)
The research presents its conception of the representations of the Iraqi identity in Iraqi plastic art after 2003, the year in which the country entered and after it a history fraught with tensions, conflicts, chaos, and the absence of political, societal and cultural stability. A perception to confront it, or even an awareness to deal with it, stems from all of that